Graph Neural Networks and Deep Reinforcement Learning in Warehouse Order Picking and Batching - Literature Review - Čelik, Nejc; Andrej Škraba, Andrej Škraba (44th International Conference on Organizational Science Development: Human Being, Artificial Intelligence and Organization, Conference Proceedings, 2025)
This paper is a systematic literature review on use of the Deep Reinforcement Learning (DRL) and Graph Neural Networks (GNN) in warehouse. We first explore the use of DRL and GNN for optimization of order picking and batching in warehouse. Because of very little results on use of GNNs in optimization of order picking and batching we extended our search to general use of GNNs in warehouse environment. We identified different topics of research using Latent Dirichlet Allocation (LDA) and identified main problems in use of DRL and GNNs in warehouse environment.